A New Measuring Method of Manufacturing Error for Cycloid Gear of Robot RV Reducer - Zhou Junxiang; Li Tianxing; Wei Bingyang; Deng Xiaozhong; Zhou Guangcai; Wang Guofeng; Xing Chunrong (Jixie chuandong, 2017)
A new measuring method setting the node as single tooth reference point for manufacturing error of cycloid wheel is proposed. The theoretical model and error measurement model of the cycloid wheel drive are established. The measurement path is planned,and measurement driver software is developed. By using the meshing principle of the pin-swing drive and the measuring theory of the complex surface,the manufacturing error of the cycloidal wheel is obtained. The tooth profile and pitch deviation of the fact cycloidal profile are measured on the domestic gear measuring center. The measurement results under different reference points are compared and the correctness of the new method is verified.